IMPACT OF NEIGHBORHOOD RESOURCES ON HOMEBOUND STATUS. (11th November 2018) - Ornstein, K; Garrido, M; Siu, A
Abstract: A growing population of individuals with multimorbidity, cognitive impairment and functional decline live in the community but are homebound, defined as rarely or never leaving home. Homebound status is associated with decreased access to medical services and poor health outcomes. The goal of this study was to understand whether neighborhood resources enabled individuals to delay homebound status and remain in the community. Using the National Health and Aging Trends Study (NHATS), a nationally representative sample of Medicare beneficiaries, linked to the U.S. Census, Dartmouth Atlas, Area Health Resource Files (AHRF) and LTCFocus, we followed 7042 initially non-homebound community-dwelling older adults for 5 years. We used Cox Proportional Hazards Models to predict time to homebound status, censoring for death, loss to follow up and nursing home status, adjusting for NHATS analytic weights. In analyses controlling for clinical characteristics (e.g., dementia status, function) and demographic factors (e.g., individual income, education, urbanicity, caregiving resources), availability of nursing home beds and primary care providers and walkability did not impact risk of becoming homebound. High neighborhood SES was protective against homebound status, although this relationship was attenuated in fully adjusted models (HR = .80; p=.07). Those living in areas with more homecare agencies had higher hazards of becoming homebound (p<.01). Homebound status is an understudied adverse outcome for older adults that may be dependent on neighborhood resources. Understanding relationships among neighborhood characteristics and homebound risk may lead to identification of targets for interventions/policies to allow older adults to maintain independence and interaction with the community.